Treatment of a Large Gastric Phytobezoar With Coca-Cola, Cellulase, and Endoscopic Fragmentation in a Community Hospital - Jaewon Song; Dong Yeol Shin (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Bezoars are indigestible masses that can cause gastrointestinal complications such as obstructions and perforations. We report the case of a 60-year-old man with a history of type 2 diabetes mellitus and duodenal ulcer surgery. The patient developed a large gastric phytobezoar that caused persistent dyspepsia and epigastric pain. Upper endoscopy confirmed a 10-cm phytobezoar and a 1.5-cm active ulcer at the gastric angle. To soften the bezoar, Coca-Cola and cellulase were administered to the patient. This treatment significantly reduced the bezoar’s hardness, permitting its successful endoscopic fragmentation using conventional devices. Over three endoscopic sessions, the bezoar was fragmented into pieces smaller than 1 cm and removed; thereafter, the gastric ulcer healed completely. This case illustrates the effectiveness of combining the actions of Coca-Cola and cellulase with endoscopic methods to treat large bezoars, providing an alternative to surgical approaches in community healthcare settings.